Penyuluhan Manajemen Kualitas Produk Pada Umkm Desa Wanakerta, Kec. Sindang Jaya Kabupaten Tangerang, Banten - Al Faroqi, Fachmi; Atmaja, Sena; Hadi, Helmas Septiyo; Maesaroh, Siti (Yayasan Daarul Huda Kruengmane, 2025)
MSME have relatively more limitations compared to large companies, especially in quality management. In food products, the level of product safety produced is one of the most important indicators in assessing product quality. The problems that exist in MSME in Wanakerta Village are the low understanding of product quality management and the low understanding of SOP. Counseling is carried out by providing materials by speakers and training in product quality management and making SOP accompanied by discussions. In this counseling, direct interaction between speakers and participants is important. Participants are invited to discuss, ask questions, and share experiences, so that they can understand the concepts taught better. The results of the counseling are (1) MSME participants have better knowledge of product quality standards/4P, including products that adjust to target markets, attractive advertising, affordable prices; (2) MSME participants understand the creation of product SOPs and ensure that the production process is consistent according to SOPs